Role of satellite glial cells in gastrointestinal pain - Hanani, Menachem (Frontiers in Cellular Neuroscience, 2015)
Gastrointestinal (GI) pain is a common clinical problem, for which effective therapy is quite limited. Sensations from the GI tract, including pain, are mediated largely by neurons in the dorsal root ganglia (DRG), and to a smaller extent by vagal afferents emerging from neurons in the nodose/jugular ganglia. Neurons in rodent DRG become hyperexcitable in models of GI pain (e.g., gastric or colonic inflammation), and can serve as a source for chronic pain. Glial cells are another element in the pain signaling pathways, and there is evidence that spinal glial cells (microglia and astrocytes) undergo activation (gliosis) in various pain models and contribute to pain. Recently it was found that satellite glial cells (SGCs), the main type of glial cells in sensory ganglia, might also contribute to chronic pain in rodent models. Most of that work focused on somatic pain, but in several studies GI pain was also investigated, and these are discussed in the present review. We have shown that colonic inflammation induced by dinitrobenzene sulfonic acid (DNBS) in mice leads to the activation of SGCs in DRG and increases gap junction-mediated coupling among these cells. This coupling appears to contribute to the hyperexcitability of DRG neurons that innervate the colon. Blocking gap junctions (GJ) in vitro reduced neuronal hyperexcitability induced by inflammation, suggesting that glial GJ participate in SGC-neuron interactions. Moreover, blocking GJ by carbenoxolone and other agents reduces pain behavior. Similar changes in SGCs were also found in the mouse nodose ganglia (NG), which provide sensory innervation to most of the GI tract. Following systemic inflammation, SGCs in these ganglia were activated, and displayed augmented coupling and greater sensitivity to the pain mediator ATP. The contribution of these changes to visceral pain remains to be determined. These results indicate that although visceral pain is unique, it shares basic mechanisms with somatic pain, suggesting that therapeutic approaches to both pain types may be similar. Future research in this field should include additional types of GI injury and also other types of visceral pain.